PERBEDAAN TEKANAN INTRAOKULAR DAN RADANG KORNEA PADA PEMBERIAN TETES MATA DEKSAMETASON DIBANDING FLUOROMETOLON PASCA PRK - , Rinanto Prabowo ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Photorefractive keratectomy (PRK) is generally believed to be safe and effective for treatment of myopia. Corneal inflammation after PRK have been reported as the common complication, so that the use of topical steroids are mandatory. Certain studies have reported the topical steroid effectiveness. Previous studies found that topical steroids are safe to suppress the inflammatory process after PRK. One drawback is that steroid responders may develop elevated intraocular pressure (IOP). The potential ocular hypertensive effect of corticosteroid has limited their prolonged use. Dexamethasone is strong anti-inflammatory drugs that have tendency to raise intraocular pressure higher than fluorometholone. To compare the intraocular pressure (IOP), degree of blepharospasme, conjunctival hyperemia, watering, and postoperative pain following the use of dexamethasone and fluorometholone for suppressing inflammatory process after PRK. A clinical trial was carried out in 34 patients with myopia > -4 D. In 34 eyes after PRK using topical steroid with dexamethasone and 34 eyes with fluorometholone. Follow up were taken at day 2, 7, 14, 30, 60 postoperatively. Standardised examination was used to assess IOP, degree of blepharospasme, conjunctival hyperemia, watering, and postoperative pain were assessed using visual analogue scale. No significant difference was found in intraocular pressure between both group (p>0,05). There was no significant difference of VAS score between both group at all follow ups (p>0,05). Degree of blepharospasme, conjunctiva hyperemia, and watering was not significant different between both group at all follow ups (p>0,05). We concluded that there was no significant difference in intraocular pressure, degree of pain, blepharospasme, conjunctiva hyperemia, and watering between dexamethasone and fluorometholone group.